EVALUATION OF THE IMPLEMENTATION OF FORMATIVE ASSESSMENT OF SCIENCE SUBJECTS IN JUNIOR HIGH SCHOOLS - Pramesti, Alya Rifda; Sabtiawan, Wahyu Budi (Universitas Bhinneka PGRI, 2025)
The use of formative assessment in learning is a way that can be done to improve the quality of students. This study aims to describe the evaluation of the application of formative assessment in Natural Sciences (IPA) subjects. The research method used is a mixture using the explanatory sequential design. The population used includes all students and science teachers of Junior High Schools (SMP) in Surabaya. The sample used in this study was science teachers and students in grades 7 to 9 of SMP Negeri 62 Surabaya. Data were collected through documentation, observation, and questionnaires. The results of this study indicate, among others: (1) at the information collection stage, it is included in the sufficient category, (2) information processing and interpretation are included in the sufficient category, and (3) action taking is included in the high category. So it can be concluded that formative assessment evaluation has been implemented at SMP Negeri 62 Surabaya, which is indicated by teachers and students who are able to apply feedback, peer assessment, and self-assessment well.